Selection intensity for milk yield in 1970—1977 in the Finnish Ayrshire - Lindström, U. B. (Agricultural and Food Science, 1978)
Selection differentials for sires and dams of bulls taken into AI use in 1970—1977, as well as for sires used in AI, were combined with an estimate of the quality of dams of female replacements to calculate the (predicted) genetic change in milk yield in the Ayrshire breed. In the period the average annual genetic gain was 0.97 % of the mean yield, in the last three years it was c. 1.1 %. The average generation interval was 6.8 years; 8.7 years for the bull sires, 7.4 years for the bull dams and 6.4 years for the cow sires. The bull sires accounted for 42 %, the bull dams for 37 % and the cow sires for only 12% of the total genetic gain. A more rational use of progeny tested and young bulls, combined with a reduction of the generation interval of 15 %, could easily have increased the genetic progress by 20 %.